Phytochemical constituents and cytotoxic activity of Physalis angulata L. growing in Vietnam. (October 2018) - Tuan Anh, Hoang Le; Thao, Do Thi; Dung, Duong Thi; Kiem, Phan Van; Quang, Tran Hong; Hai Yen, Pham Thi; Tuan, Do Thanh; Cuong, Pham Viet; Viet Cuong, Le Canh; Hung, Tran Manh
Graphical abstract: Highlights: Eight compounds including two new withanolides, physagulins P and Q were isolated from Physalis angulata . Their chemical structures were identified by spectroscopic data interpretation comprising 1D, 2D NMR and MS data. The cytotoxic activity of these metabolites was investigated against A549, HeLa, and PANC-1 cancer cell lines. Abstract: A comprehensive phytochemical investigation of the dichloromethane-soluble fraction of Physalis angulata led to the isolation of eight compounds (1–8 ) including two new withanolides named physagulin P and Q (compounds5 and8 ). Their chemical structures were established using two-dimensional nuclear magnetic resonance (spectroscopy. The cytotoxic activity of these metabolites was investigated against A549, HeLa, and PANC-1 cancer cell lines. Among them, compound1 showed significant cytotoxic activity against A549 cells with a half-maximal inhibitory concentration (IC50 ) value of 8.27 μM, while compound7 showed the most potent activity against PANC-1 cells with an IC50 value of 3.18 μM.